Empowering farmers through participatory plant breeding: An initiative of the green foundation - Ramprasad, Vanaja; Shibu, M.P. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
In the so-called difficult environments, institutional plant breeding appears to be a failure, mainly because breeding is directed at increasing yields in more favorable environments. Although the improved varieties have broad adaptability, under varied marginal environments, they do not express their yield potential or they do not satisfy other user requirements. In any environment, the potential of a plant is controlled by the interaction of its genetic composition with the environment. This involves adaptation of the plant lo both physical environments (climate, soil, abiotic and biotic stress) and the socioeconomic environment (user concerns, consumers' preferences, economic status, markets, etc.). After the introduction of high-yielding varieties and hybrids during the green Revolution in India, hundreds of landrace. And indigenous varieties have become extinct or on the verge of extinction, largely because they have not been considered economical to grow under the present market economy.